PERLINDUNGAN KONSUMEN TERHADAP PENGGUNAAN SEPEDA LISTRIK - Teguh Rama Prasja; Esy Kurniasih (Jurnal Kajian Ilmu Hukum, 2025)
The objectives of this research are, first, to examine the legal regulations regarding the use of electric bicycles in Indonesia from the perspective of Law No. 22 of 2009 on Road Traffic and Transportation and other relevant regulations, and second, to analyze the forms of legal protection for consumers of electric bicycles in the event of accidents or losses caused by product defects or negligence of business actors.The research method employed is normative juridical, using a statutory approach and a case approach concerning the use of electric bicycles and the scope of consumer protection for their users.The findings of this research indicate, first, that the regulation of electric bicycles in Indonesia remains incomplete, as it is only partially regulated under Minister of Transportation Regulation No. 45 of 2020. The absence of explicit provisions in higher-level legislation, such as the Road Traffic and Transportation Law (UU LLAJ), creates a legal vacuum that results in uncertainty regarding the status of electric bicycles in traffic law and consumer protection.Second, a clear legal framework within statutory regulations is essential to provide legal certainty, ensure product feasibility standards in accordance with SNI, and guarantee consumer protection against potential losses and safety risks. Without adequate regulation, consumers remain vulnerable to harm, both in terms of product quality and road safety.